Characteristics of modern technologies in the training and competitive process of elite athletes in sports games - Нагорна В. О.; Митько А. О.; Борисова О. В.; Шляпнікова І.; Жигайлова Л. В. (Спортивна наука та здоров'я людини, 2024)
The examination of sports science literature and expert assessments unveils predominant trends in the utilization of innovative technologies in elite sports, with a particular emphasis on the widespread adoption of wearable technology, biomechanics and motion analysis, and recovery and regeneration techniques. The outcomes from OpenCap biomechanical analysis show a high correlation (r=0.99, α = 0.05) between the symmetry of knee joint angles during barbell squats by elite athletes, confirming the efficacy of real-time monitoring exercise techniques. The Romberg coefficient of 194.5% ± 2.47 indicates a notable degree of stability among elite athletes. Conclusions. This study enhances the comprehension of innovative technologies, exemplified by OpenCap biomechanical analysis, and their effectiveness in optimizing the training performance and competitive outcomes of elite athletes in sports games. The findings provide valuable insights for coaches, sports scientists, and researchers aiming to optimize training methods and elevate athlete performance in sports games.
Characteristics of modern technologies in the training and competitive process of elite athletes in sports games / V. Nagorna, A. Mytko, O. Borysova, I. Shlyapnikova, L. Zhyhailova // Спортивна наука та здоров'я людини: наукове електронне періодичне видання. - К., 2024. - № 1 (11). - С. 14-25.
Keywords: sports games; innovational technologies; OpenCap; wearable sensor technologies; artificial intelligence